Quality Assurance in Higher Education Institutions: Exist Survey among Universiti Putra Malaysia Graduating Students - Konting, Mohd Majid; Kamaruddin, Norfaryanti; Man, Nor Azirawani (Canadian Center of Science and Education, 2009)
This paper presents the exit survey of graduating students at Universiti Putra Malaysia (UPM). The results gathered from 1,823 final year students of the 2006/07 session indicate that overall, the students’ satisfaction level is moderately high (3.55 ± 0.79). The students’ perception on the attributes of graduates resulting from learning outcomes is also moderately high (3.65 ± 0.66). Although there are no differences in students’ satisfaction level according to gender (t = .582, p > 0.05) and students’ residence (t = .121, p > 0.05), however, it differs according to students’ study programs (F = 35.44, p < 0.01), with Social Science students having a higher satisfaction level (3.80) compared to their counterparts in the Physical Sciences and Engineering (3.48) and Bioscience and Medicine (BSM) programs (3.37). Through this exit survey, together with many other assessment initiatives, the university aspires to provide the highest possible quality in terms of teaching, research and professional services .